Linking resting‐state networks and social cognition in schizophrenia and bipolar disorder. Issue 16 (19th July 2019) - Jimenez, Amy M.; Riedel, Philipp; Lee, Junghee; Reavis, Eric A.; Green, Michael F.
Abstract: Individuals with schizophrenia and bipolar disorder show alterations in functional neural connectivity during rest. However, resting‐state network (RSN) disruptions have not been systematically compared between the two disorders. Further, the impact of RSN disruptions on social cognition, a key determinant of functional outcome, has not been studied. Forty‐eight individuals with schizophrenia, 46 with bipolar disorder, and 48 healthy controls completed resting‐state functional magnetic resonance imaging. An atlas‐based approach was used to examine functional connectivity within nine RSNs across the cortex. RSN connectivity was assessed via nonparametric permutation testing, and associations with performance on emotion perception, mentalizing, and emotion management tasks were examined. Group differences were observed in the medial and lateral visual networks and the sensorimotor network. Individuals with schizophrenia demonstrated reduced connectivity relative to healthy controls in all three networks. Individuals with bipolar disorder demonstrated reduced connectivity relative to controls in the medial visual network and connectivity within this network was significantly positively correlated with emotion management. In healthy controls, connectivity within the medial and lateral visual networks positively correlated with mentalizing. No significant correlations were found for either visual network in schizophrenia. Results highlight the role of altered early visual processing in social cognitive deficits in both schizophrenia and bipolar disorder. However, individuals with bipolar disorder appear to compensate for disrupted visual network connectivity on social cognitive tasks, whereas those with schizophrenia do not. The current study adds clarity on the neurophysiology underlying social cognitive deficits that result in impaired functioning in serious mental illness.